Banana-pseudostem sap growing media as a novel source of phytochemicals and mineral nutrients: influence on seedling growth of sweet corn - Islam, Mahammad Shariful; Kasim, Susilawati; Mohd Amin, Adibah; Tan, Geok Hun; Alam, Md. Khairul; Haque, Mohammad Amdadul (Instituto de Investigaciones Agropecuarias, INIA, 2021)
Phytochemicals in plant extracts help plants to grow, develop and survive. This study aimed to identify the phytochemicals and quantify soluble nutrients present in banana (Musa acuminata Colla)-pseudostem sap, and to observe the subsequent effect on seedling growth of sweet corn (Zea mays L. var. saccharata (Sturtev.) L.H. Bailey). The collected banana pseudostem sap was extracted with methanol followed by a liquid-liquid extraction procedure. The extracted fractions were analyzed by liquid chromatography mass spectrometry (LC-MS). Seven concentrations of fresh banana pseudostem sap, i.e., 5%, 10%, 15%, 25%, 50% aqueous, and 100% raw sap with control (distilled water) were replicated three times following a completely randomized design. The LC-MS analysis identified 86 various phytocompounds, while inductively coupled plasma (ICP) quantified different essential plant nutrients in the fresh sap, confirming the benefits of phytocompounds and mineral nutrients on sweet corn. The sap showed 44 beneficial plant compounds such as 1-amino-1-carboxycyclopropane, 4-aminobenzoic acid, glutamic acid, 1,4-benzoquinone, proline betaine, butanoic acid, hydroxysouric acid, 2,4-dihydroxybenzoic acid and aluminium acetate. These are vital for plant growth and development. The results confirmed that a high number of beneficial secondary metabolites and mineral nutrients in aqueous banana pseudostem sap, especially in lower concentrations (5%-15%), significantly influenced seedling growth over higher concentration and control. However, compared to control, 10% aqueous banana pseudostem sap resulted in 21.2% larger root length, 19.6% shoot length, 32.0% dry biomass, and 17.4% chlorophyll content, respectively. It is concluded that a 10% aqueous solution of fresh banana pseudostem sap will be more effective for crop production.